PERBANDINGAN PEMANFAATAN JURNAL TERCETAK DENGAN JURNAL ELEKTRONIK UNTUK KEBUTUHAN INFORMASI MAHASISWA DI PERPUSTAKAAN UNIVERSITAS SUMATERA UTARA CABANG KEDOKTERAN - nur aini (Jurnal Pustaka Nusantara dan Budaya, 2013)
This study aims to compare the use of print journals with electronic journals for the information needs of students at the University of Sumatera Utara Branch Library of Medicine. Analysis includes the use of journals, journal collections conformity with the needs of the user. The research method used is descriptive research with a comparative approach. In determining the sample used technique accidental. The data was collected through observation and questionnaires to students Bachelor’s Degree General Medicine Program. Analyses were performed by grouping data from questionnaires and observation. This study shows the results of a comparison the use of printed journals with electronic journals, the majority of students often take advantage of electronic journals than print journals. Number of electronic journals in general to meet the information needs of students rather than the printed journal. In general, students expressed more sophisticated electronic journals than print journals.